Rare earth elements for enhancing photocatalysis in pollutant degradation and water treatment - Zheng, A. L. T.; Sinin, A. E.; Jin, W. T.; Feng, K. L.; Boonyuen, S.; Chung, E. L. T.; Lease, J.; Andou, Y. (Springer Nature, 2025)
This review examines recent progress in using rare earth-based photocatalysts and their composites to degrade environmental pollutants. Rare earth elements (REEs), recognized for their unique electronic configurations and exceptional optical properties, have become effective dopants and co-catalysts, enhancing the capabilities of traditional semiconductor photocatalysts. Key enhancement strategies, including doping, co-doping, surface functionalization, and heterostructure formation, are analyzed to illustrate how they improve photocatalytic efficiency, stability, and selectivity. The review details studies on the photocatalytic degradation of various pollutants, such as dyes, antibiotics, and pesticides. It highlights how REEs contribute to better light absorption, efficient charge separation, and increased reactive oxygen species (ROS) production. The review also addresses challenges with the long-term stability of doped photocatalysts, like structural degradation and dopant leaching, suggesting possible solutions to enhance durability. By providing a broad overview, this review aims to guide researchers in designing next-generation photocatalysts for environmental remediation and to support the development of more sustainable water treatment technologies. Additionally, emerging trends such as green synthesis, integration with carbon-based nanocomposites, and scalable photocatalytic applications stressed REEs’ potential in advancing eco-friendly water treatment solutions, aligning with global sustainability objectives.